FEATURES OF ORGANIZING NUTRITION, WATER SUPPLY, AND SANITARY-HYGIENIC SUPPORT FOR SERVICEMEN IN HOT CLIMATES AND HIGH-ALTITUDE CONDITIONS (World Bulletin of Public Health, 2026)
This article examines the deployment, nutrition, and water supply of military personnel in extreme desert and high-altitude conditions. The effects of high temperature, direct solar radiation, hypoxia, and limited water availability on physical, cognitive, and combat performance are analyzed. Data indicate a 20–40 % increase in daily energy expenditure in hot and high-altitude climates, highlighting the risk of dehydration, heat exhaustion, and altitude sickness
Keywords: extreme climate; desert; high altitude; military personnel